PROGRAM SPEAKING CLASS SEBAGAI SARANA PEMBERDAYAAN SANTRI PUTRI PONDOK HUTAN AGU PATTANI THAILAND - Nurhaliza Anggraini; Asep Sunarko; Marwiati; Ahmad Faizun; Achmad Affandi (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to evaluate the effectiveness of the speaking class program at Pondok Hutan Agu Pattani, Thailand, in empowering female students. The research employs a qualitative approach with a case study method, collecting data through in-depth interviews, participant observation, and documentation. Respondents include female students, speaking class teachers, and pondok administrators. Data were analyzed using thematic analysis to identify and categorize relevant themes. The results show that the speaking class program at Pondok Hutan Agu Pattani effectively enhances the English-speaking skills of the female students, with an increase in fluency from 10% to 80% and confidence from 20% to 70%. Additionally, the program successfully develops the students' interpersonal skills, such as teamwork, public speaking, and active participation in discussions. The program better prepares the students for the outside world, increasing their chances of obtaining better jobs and pursuing higher education. In conclusion, the speaking class program significantly contributes to the empowerment of female students at Pondok Hutan Agu Pattani, Thailand. The program provides them with the necessary skills and confidence to succeed in the future. Recommendations for improving the program include enhancing learning resources, providing advanced training for teachers, integrating technology into the learning process, and conducting regular evaluations.